How to relaxation of social studies learning through team quiz method? Implementation for student activeness - Zuhroh, Ni’matuz; Sari, Ulfi Andrian; Achmad, Itna Laily Rosyida; Nurfadhilah, Anisa (Abjadia : International Journal of Education, 2025)
Relaxation can be one way to cope with stress, therefore, it is important to control stress in learning. This research aims to describe the implementation of team quiz learning relaxation in improving student activeness. This research uses qualitative research methods. The data was obtained from observation, interview and documentation. The research subjects were teachers and students of MtsN Kota Malang. Data analysis with the following steps: 1) Data collection, 2) Data Condensation, 3) Data Presentation, and 4) Drawing Conclusions. The findings of this study concluded that the implementation of team quizzes was significantly able to increase student activity, which was reflected in several indicators, such as: 1) higher attendance in learning activities, 2) increased attention to teacher explanations, 3) active in discussing and collaborating in groups, 4) students' ability to express and listen to opinions, and 5) increased cooperation in planning and solving learning problems. The implications of these findings indicate that learning relaxation using the team quiz learning method can be an effective strategy in creating a more active learning environment and is able to reduce stress in students so that it can improve student academic achievement.